Efforts to Improve Children's Speaking Skills through the Use of Hand Puppets at TK Bunga Anggrek - Yuliana, Ati; Ramazaniati (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve the speaking skills of early childhood children through hand puppets using collaborative Classroom Action Research (CAR) based on the Kemmis model which was implemented in two cycles. The research subjects consisted of 13 children, namely 9 boys and 4 girls, with the object of research being speaking skills through hand puppets. Data were collected through observations using observation sheets and documentation in the form of activity notes, videos, pictures, and Daily Activity Plans (RKH), then analyzed descriptively qualitatively and quantitatively. The success criteria were determined if the children's speaking skills reached 80% with a very good category. The results of the study showed an increase in speaking skills in Group B children at Bunga Anggrek Kindergarten, where the results of observations in the pre-action stage reached 42.30%, Cycle I 57.69%, and Cycle II increased to 91.03%, thus meeting the success criteria. The steps implemented included the teacher telling stories using hand puppets, dividing children into groups of three children, children repeating the story told by the teacher, and the teacher providing motivation and awards in the form of "Star Signs". This study proves that the use of hand puppet media is effective in improving the speaking skills of early childhood children, while also fostering active participation, courage, and children's confidence in speaking in front of peers, so that this strategy can be used as an interesting and interactive learning model in early childhood education.